Antiproliferative Activity of microRNA-125a and its Molecular Targets - Russo, Aniello; Potenza, Nicoletta (MicroRNA, 2019)
Background: MicroRNA-125a is present in all animals with bilateral symmetry and displays a conserved nucleotide sequence with a section of 11 bases including the seed region that is identical in all considered species. It primarily downregulates the expression of LIN28, thereby promoting cell differentiation and larval phase transitions in nematodes, mammals and insects. Objective: In this review, we focus on the cellular control of miR-125a expression and its antiproliferative activity. Results: In mammalians, microRNA-125a is present in most adult organs and tissues in which it targets proteins involved in the mitogenic response, such as membrane receptors, intracellular signal transducers, or transcription factors, with the overall effect of inhibiting cell proliferation. Tissue levels of miR-125a generally raise during differentiation but it is often downregulated in cancers, e.g. colon, cervical, gastric, ovarian, lung, and breast cancers, osteosarcoma, neuroblastoma, glioblastoma, medulloblastoma, retinoblastoma and hepatocellular carcinoma. Conclusion: The antiproliferative activity of miR-125a, demonstrated in many cell types, together with the notion that this miRNA is downregulated in several kinds of cancers, give a substantial support to the concept that miR-125a plays an oncosuppressive role.
Keywords: microRNA